A Reconfigurable Millimeter-Wave Antenna Array With Wide-Range Continuous Beamwidth Control (WCBC) Based on Polarization-Mixing - Zeng, Fanchao; Ding, Can; Guo, Y. Jay (IEEE transactions on antennas and propagation, 2024)
This article presents a reconfigurable millimeter-wave (mm-wave) dual-polarized antenna array system featuring wide-range continuous beamwidth control (WCBC) using the polarization-mixing method. By simultaneously exciting dual polarizations, the system achieves wider beams, with a continuously adjustable beamwidth ranging from 21° to 100°. Additionally, the system retains its original beam scanning capabilities when using the two polarizations separately. Importantly, the ability in flexible beam scanning and wide beamwidth tuning is accomplished with only phase shifters without the need for amplitude control. All antenna elements are fully excited, ensuring high overall efficiency. The robustness and stability of the system are confirmed through error analysis. The WCBC array system is designed, fabricated, and experimentally validated. By employing a control circuit, it realizes reconfigurable dual functionality, i.e., beam scanning and wide beamwidth variation, in a simple and cost-effective manner.